Mechanisms and origins of the switchable regioselectivity of FeBr3-catalyzed [1, 2]-aryl and [1, 2]-alkyl shifts of α-aryl aldehydes. Issue 8 (29th January 2016) - Liu, Congcong; Liu, Yuxia; Tang, Yanan; Liang, Haosheng; Bi, Siwei
Abstract : With the aid of DFT calculations, the FeBr3 -catalyzed skeletal rearrangements of 2-cyclohexanal, 2- p -C6 H4 OMe-propylaldehyde (1A ) and 2-phenyl, 2- p -C6 H4 OMe-propylaldehyde (1B ) were investigated theoretically. Abstract : With the aid of DFT calculations, the FeBr3 -catalyzed skeletal rearrangements of 2-cyclohexanal, 2- p -C6 H4 OMe-propylaldehyde (1A ) and 2-phenyl, 2- p -C6 H4 OMe-propylaldehyde (1B ) were investigated theoretically. As compared to mono-FeBr3 as a catalyst, the bis-FeBr3 serving as a catalyst is found to be not only enhancing the catalytic efficiency but also improving the product selectivity. For the reaction starting from 1A, the [1, 2]-group shift (first step) is rate-determining, and why the Cy shift is the most favored is rationalized in comparison with the p -C6 H4 OMe and Me shifts. For the reaction starting from 1B, the [1, 2]-H shift (second step) is rate-determining although the [1, 2]- p -C6 H4 OMe shift is favored over the [1, 2]-phenyl shift. In contrast to the experimental proposal, the newly established H2 O/Br − joint-assisted H-shift mechanism explains the partial α-H source of the [1, 2]-Cy shift product. In addition, we discussed the inherent mechanism that explains why both the [1, 2]- p -C6 H4 OMe and [1, 2]- p -C6 H4 CF3 shifts are more facile than the [1, 2]-phenyl shift although the substituents –OMe and –CF3 have opposite electronic behaviors.